First detection of Bursaphelenchus abietinus and B. andrassyi in Italy. Issue 5 (19th August 2020) - Torrini, Giulia; Paoli, Francesco; Mazza, Giuseppe; Simoncini, Stefania; Strangi, Agostino; Guidotti, Alessandro; Mori, Emiliano; Roversi, Pio Federico; Marianelli, Leonardo
Abstract: During the annual monitoring surveys for the pinewood nematodes, Bursaphelenchus xylophilus, conducted in the Tuscany region (Central Italy) from the year 2015 to 2019, a total of 1, 025 wood samples were collected from symptomatic plants in coniferous forests. Among the eight Bursaphelenchus species found, Bursaphelenchus abietinus and B. andrassyi were identified through morphological and molecular analysis and recorded for the first time in Italy. Additionally, new associations between Bursaphelenchus species and the host plants or insect vectors have been reported. The generalized linear models performed to investigate the possible relation between the level of coniferous plant decay and the occurrence of Bursaphelenchus nematodes highlighted that the probability of the Bursaphelenchus presence in the samples increased with the degeneration of the phytosanitary state of the tree, the presence of blue stain fungi and different types of insects.